한국에서 자생하는 갈조식물문에 관한 본초학적 연구 - 전의상; Ui Sang-jeon; 정종길; Jong-gil Jeong (大韓本草學會誌, 2021)
Objective : The purpose of this dissertation is to make a list of the phaeophyta growing naturally in the Korean coastal waters, and to carry out a survey on the current distribution status to investigate the phaeophyta which can be used as medicinal herbs. Methods : References and research papers about herbology published at home and abroad were examined. Results : The results of this study were as follows : A total of 63 genera and 145 species of phaeophyta was found in the Korean coastal waters among which 11 genera and 15 species(approximately 11%) were medicinal plants. Out of the 145 species of phaeophyta 27 species belonged to Sargassum, and out of the 15 species of medicinal plants 4 species belonged to Sargassum. Among the medicinal parts 11 species belonged to algae. Sixteen species had cold property, and 16 species had salty flavors. Thirteen species had the efficacy of liver meridian, and 15 species had the potency of YEONKYUN, which helps to remove hard clots generated in human body. No toxic drugs were detected. Conclusion : There were totaled to 63 genera and 145 species in Phaeophyta in Korea and among them medicinal plants are 11 genera, 15 species, some 11% in total. Thirteen species had the efficacy of liver meridian, and 15 species had the potency of YEONKYUN, which helps to remove hard clots generated in human body. No toxic drugs were detected.